Edukasi keamanan pangan didapur rumah tangga - Wiqayatun Khazanah (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
Food is sourced from biodiversity and water as food and beverages or as additional ingredients in food processing. Unclean food processing will focus on human health which needs to pay attention to food safety in the processing needed in the household kitchen. Food safety education is a means to provide knowledge about housewives about food knowledge of foodborne illness. By providing education to mothers who can implement good food safety in the home kitchen. This study discusses education about household kitchen safety education. This research was conducted in Darul Imarah Aceh Besar Subdistrict in October 2017. This study used a descriptive analytic design. The number of samples was 40 people who were randomly selected by strata random sampling method and data collection was done using a pretest and posttest questionnaire. Data analysis using paired t-test. The results was showed were differences between hand washing education (p= 0,000), food storage (p= 0,000), cross contamination (p= 0,036). Conclusion, there is a difference between before and after food safety education.Pangan bersumber dari hayati dan air sebagai makanan dan minuman atau bahan tambahan dalam mengolah makanan. Pengolahan makanan yang tidak bersih akan berpengaruh pada kesehatan manusia sehingga perlu memperhatikan keamanan pangan pada pengolahan terutama di dapur rumah tangga. Edukasi keamanan pangan merupakan suatu sarana untuk memberikan pengetahuan bagi ibu rumah tangga mengenai kerentanan makanan terhadap penyakit bawaan makanan. Dengan memberikan edukasi di harapkan ibu dapat menerapkan keamanan pangan yang baik di dapur rumah. Penelitian ini bertujuan untuk mengetahui pengaruh edukasi keamanan pangan di dapur rumah tangga. Penelitian ini di lakukan di Kecamatan Darul Imarah Aceh Besar pada bulan Oktober 2017. Penelitian ini menggunakan rancangan deskriptif analitik. Total sampel sebanyak 40 orang yang dipilih secara acak dengan metode strata random sampling dan pengumpulan data di lakukan menggunakan kuasioner pretest dan postest. Analisis data menggunakan paired t-test. Hasil menunjukkan perbedaan antara edukasi cuci tangan (p=0,000), penyimpanan bahan makanan (p=0,00), kontaminasi silang (p=0,036). Kesimpulan, terdapat perbedaan antara sebelum dan sesudah edukasi keamanan pangan